Socio-cultural analysis of the independent Papua Organization (OPM) and the narrative of Papua integration into Indonesia - Enty Forisna Lastaruli Manalu; Efyka Tamala Sitorus Pane; Joshua Kalebso Manalu; Neliana Lubis (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2022)
This study aims to analyse the socio-cultural organisation of the Free Papua Movement (OPM) and the narrative of the integration of Papua into Indonesia. The diversity of styles or points of view of historical writing regarding the integration of Papua into Indonesia cannot be separated from the sociology and culture of the historical writers, whether they support Indonesia, support Papua, or write based on historical facts. This study uses historical research methods consisting of heuristics, source verification or criticism, interpretation, and historiography. The study results show that integrating Papua into the Unitary State of the Republic of Indonesia (NKRI) has two different narratives. First, the version of the government of the Republic of Indonesia says that the process of integrating Papua into the territory of the Republic of Indonesia is legal and by the constitution. Second, the Free Papua Organization (OPM) version states that this is illegal and violates human rights. These two narratives are currently developing in history learning, with different intensities. Until now, Papua remains part of the Unitary State of the Republic of Indonesia.